Proceedings of the Methodological Research at the Ecoregional Level: Review Workshop - International Service for National Agricultural Research (International Service for National Agricultural Research, 1998)
The Workshop on Methodological Research at the Ecoregional Level brought together a diversity of participants. One group consisted of scientists from IARCs and NARS institutions who are leading the five methodology projects currently supported by the Ecoregional Fund. A second group comprised NARS scientists, the proponents of four proposed projects selected from among those under consideration by the Fund. A third group was made up of resource persons, of diverse disciplinary backgrounds and institutional affiliations, from both the North and South, who had been invited to enrich the discussion. A final group consisted of members of the ICASA board (which was meeting concurrently), other interested researchers and donor representatives.